Resposta de paracoccidioides a compostos candidatos a antifúngicos: ensaios in vivo e in vitro - Silva, Lívia do Carmo (2014)
Paracoccidioidomycosis (PCM) is a systemic granulomatous human mycosis caused by fungi of the genus Paracoccidioides, geographically restricted to Latin America. Inhalation of spores and fragments of mycelia, infective forms of the fungus, is a common route of infection. The PCM treatment is performed with the prolonged administration of antifungal amphotericin B, the class of sulfonamides and azoles, which are toxic. In this sense, there is a need for the identification and characterization of novel targets for antifungal drugs in Paracoccidioides well as the search for new antifungal compounds from natural or obtained by chemical synthesis sources. In order to elucidate the response of Paracoccidiodies the thiosemicarbazide derivative of camphene, analysis of the transcriptional profile of the fungus was performed after 8 hs of contact with thiosemicarbazide. The results demonstrate that Paracoccidioides induced genes related to metabolism, cell cycle and DNA processing, Biogenesis of cellular components, cell transduction / signal, defense communication and virulence, energy, protein synthesis, protein fate (folding, modification, destination mechanism), translation, and proteins not classified. In addition intensely inhibited genes related to protein synthesis. In order to evaluate the biological activity of six compounds synthesized by the reaction of Morita- Baylis- Hillman was realized to minimal inhibitory concentration assays, cytotoxicity and hemolytic potential, interaction with antifungal agents already used in the treatment of PCM. The Morita-Baylis-Hillman adducts interfered on fungal growth in a dose-dependent manner, promoted the decreased activity of mitochondrial dehydrogenases and showed synergistic interaction with bactrim. No hemolytic activity was observed despite the high toxicity found and no inhibition of Malate sintase. The results demonstrate the potential of these compounds as candidates antifungal.